Hedonic Capacity in the Broader Autism Phenotype: Should Social Anhedonia Be Considered a Characteristic Feature? - Novacek, Derek M.; Gooding, Diane C.; Pflum, Madeline J. (Frontiers in Psychology, 2016)
Impairments in social motivational processes may partially explain the differences in social interaction seen among individuals with autism spectrum disorder (ASD). The social motivation hypothesis would predict an association between reduced hedonic capacity and ASD. However, to date, findings have been mixed regarding hedonic deficits among individuals with ASD; adults report lower levels of both social and physical pleasure whereas adolescents only report experiencing lower social pleasure. Moreover, previous studies examining the association between anhedonia and autistic traits have not used measures of hedonic response or taken temporal aspects of pleasure into account. The present study examined associations between autistic traits and the experience of pleasure using a nonclinical sample of young adults to further clarify the nature of hedonic deficits in the broader autism phenotype (BAP). Results revealed that autistic traits were negatively associated with both the experience of social pleasure as well as general pleasure, although the association was stronger for social pleasure. Regression analyses revealed that reduced social pleasure was a better predictor of autistic traits than general pleasure. Together these findings suggest that reduced social hedonic capacity is associated with autistic traits in the general population and should be included in conceptualizations of the BAP.